Sistem Informasi Peminjaman Dan Penggunaan Mobil Dinas Berbasis Web Pada Dinas Pemajuan Masyarakat Adat Provinsi Bali - I Nyoman Yudi Anggara Wijaya; I Gede Juliana Eka Putra; I Made Suka Danawan, I Made Suka Danawan (Primakara University, 2024)
Against the background of the absence of an information system for borrowing and using vehicles where the data processing process still uses the manual method, this application is a solution in the application of a computerized system. This research emphasizes borrowing and using vehicles only, which is expected to make work more efficient and easier, especially in the division that manages the lending of official vehicles. The system for borrowing operational official vehicles at the Bali Province PMA Office is currently still using the manual method, namely by filling out a paper form and asking for approval for a superior's signature, according to the author, it is still not effective. Reports that are only in hardcopy form, which is likely to be scattered, will have an impact at a later date if you want to check the previous period's reports again. So, from the description above, the authors draw conclusions about the use of information technology to create a system that can overcome existing problems with the System Development Life Cycle (SDLC) method for making applications using the Laravel 9 framework, and assisted by the application of Boostrav.